Assessment of Student Learning Needs Fulfillment and Autonomy in Teacher Teaching Practices - Dadang Sukirman; Della Amelia (Universitas Pendidikan Ganesha, 2023)
The existence of student autonomy in learning and the fulfillment of student learning needs is the main characteristic and key to creating student-centered learning. The distribution of learning independence and completing students' learning needs are two core indicators of student-centered learning. This study analyzes students' perceptions of how far teachers have fulfilled their learning needs and distributed autonomy in managing the learning process. 235 students (110= = male; 125 = female) from public secondary schools in Bandung, which implement Kurikulum Merdeka, were involved as the research subject. The data was gathered by survey method through a Likert-style questionnaire consisting of 25 behavioral descriptions that described teacher teaching behavior to facilitate students' learning needs and autonomy and were then analyzed by quantitative descriptive method. Study findings show that overall, students perceived teachers' capability to meet their learning needs and distribute freedom as low. Furthermore, there is no significant difference in perception between male and female students.